Sustainability of Hoteliers' strategies during endemic / Rohayu Ab Majid ... [et al.] - Ab Majid, Rohayu; Said, Rosli; Rosman, Siti Hasniza; uhana Ismail, Suhana (2022)
The arrival of COVID-19 has greatly affected real estate growth, especially commercial properties. Thus, hotel properties which were successful in providing high returns before, now have to find the best strategy to strengthen their business operations. Although it has entered the endemic era, visitors are still careful in choosing the best hotel for their accommodation. Accordingly, this study aims to examine the best strategy for the continuation of their business agenda. This study involves a questionnaire that focuses on seven main strategies (MS) along with 31 sub strategies (SS) which are distributed to 50 hoteliers throughout Malaysia. The research data were analysed using descriptive and inferential statistics. All 31 SS have employed reliability test, followed by the mean score observation to see the current strategies practiced by the hoteliers. The reliable strategies were reviewed through significant status and an indication of the correlation value. The results of the study show that only eight strategies contribute to the hoteliers' efforts to sustain their business operations in this endemic era.